2009
DOI: 10.1007/s10637-009-9281-1
|View full text |Cite
|
Sign up to set email alerts
|

Nelfinavir induces mitochondria protection by ERK1/2-mediated mcl-1 stabilization that can be overcome by sorafenib

Abstract: The HIV protease inhibitor nelfinavir is an investigational drug for cancer treatment. We have previously demonstrated induction of apoptosis by nelfinavir even in chemo-resistant ovarian cancer cells. In contrast to the pro-apoptotic effect of nelfinavir on human cancer cells, we noticed a significant upregulation of the anti-apoptotic mitochondrial membrane protein mcl-1 by nelfinavir, resulting in a mitochondria-independent induction of apoptosis. Upregulation of mcl-1 was associated with enhanced phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…Some previous studies have indicated the inhibition of proteasomal activity by HIV protease inhibitors, including nelfinavir [26,28]. The fact that nelfinavir has no influence on expression of the proteasome-regulated NF-κB inhibitor IκB (Figure 4), however, indirectly suggests that nelfinavir has no effect on the proteasomal activity of breast cancer cells.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Some previous studies have indicated the inhibition of proteasomal activity by HIV protease inhibitors, including nelfinavir [26,28]. The fact that nelfinavir has no influence on expression of the proteasome-regulated NF-κB inhibitor IκB (Figure 4), however, indirectly suggests that nelfinavir has no effect on the proteasomal activity of breast cancer cells.…”
Section: Resultsmentioning
confidence: 85%
“…We have previously described an upregulation of the anti-apoptotic mcl-1 protein by nelfinavir in ovarian cancer cells [26], but this could only be observed in one (MDA-MB-435) of the four tested breast cancer cell lines. Nelfinavir has further been described as reducing AKT phosphorylation, resulting in enhanced radiosensitivity [11,16] - which could be of special importance for breast cancer treatment, for which radiotherapy can be applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PI3/Akt/mTOR pathway plays a critical role in HCC [16] and combined inhibition of that pathway plus RAF and/or angiogenesis inhibition that is mediated by sorafenib, could act synergistically in blocking the cell growth of tumor cells [17]. Furthermore, the in vitro combination of the HIV protease inhibitor nelfinavir, with sorafenib resulted in induction of apoptosis in ovarian cancer and leukemia cell lines suggesting a possible synergistic effect of also that combination [18,19].…”
Section: Discussionmentioning
confidence: 99%